2004
DOI: 10.1074/jbc.m403935200
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Poly-α 2,8-Sialic Acid Mimotopes from a Random Phage Peptide Library and Analysis of Their Bioactivity

Abstract: Poly-␣ 2-8 sialic acid (PSA), attached to the neural cell adhesion molecule, is a permissive determinant for numerous morphogenetic and neural plasticity processes, making it a potential therapeutic target. Here, using a monoclonal antibody specific for PSA, we screened a phage-display library and identified two cyclic nine-amino acid peptides (p1, p2) that are PSA epitope analogues. We evaluated their bioactivity in vitro and in vivo. In culture, micromolar concentrations of the peptides promoted axon growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…The improved learning associated with increased NCAM PSA expression is not surprising given that the numerical frequency of polysialylated dentate neurons is directly correlated with task performance (Sandi et al, 2004;Murphy et al, 2006). The majority of newly synthesized PSA seems to be associated with the synapse-specific NCAM 180-kDa isoform (Doyle et al, 1992), and this would serve to reduce cell-cell signaling and facilitate synapse remodeling (Rutishauser, 2008), a suggestion reinforced by the learning deficits observed in mice that are deficient for the adult form of polysialyltransferase (ST8SiaIV/PST-1) (Markram et al, 2007) and the enhanced consolidation of this paradigm by post-training infusions of a cyclic oligopeptide that acts as a non-competitive agonist of PSA (Torregrossa et al, 2004;Florian et al, 2006). Moreover, facilitation of PSA activation by cognition-enhancing drugs, such as the H 3 receptor antagonist GSK189254, may have implications for the treatment of neurodegenerative conditions as, in Alzheimer's disease, the natural autoprotective response to age-related cognitive deficits is a small, but significant, activation of dentate polysialylated cell frequency (Mikkonen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The improved learning associated with increased NCAM PSA expression is not surprising given that the numerical frequency of polysialylated dentate neurons is directly correlated with task performance (Sandi et al, 2004;Murphy et al, 2006). The majority of newly synthesized PSA seems to be associated with the synapse-specific NCAM 180-kDa isoform (Doyle et al, 1992), and this would serve to reduce cell-cell signaling and facilitate synapse remodeling (Rutishauser, 2008), a suggestion reinforced by the learning deficits observed in mice that are deficient for the adult form of polysialyltransferase (ST8SiaIV/PST-1) (Markram et al, 2007) and the enhanced consolidation of this paradigm by post-training infusions of a cyclic oligopeptide that acts as a non-competitive agonist of PSA (Torregrossa et al, 2004;Florian et al, 2006). Moreover, facilitation of PSA activation by cognition-enhancing drugs, such as the H 3 receptor antagonist GSK189254, may have implications for the treatment of neurodegenerative conditions as, in Alzheimer's disease, the natural autoprotective response to age-related cognitive deficits is a small, but significant, activation of dentate polysialylated cell frequency (Mikkonen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the recent development of PSA-NCAM mimotope peptides, which may be promising therapeutic drugs for the treatment of mood disorders (Cambon et al, 2004;Torregrossa et al, 2004). Future directions should include the study of PSA-NCAM expression in the brains of depressed patients and research directed to deepen into the molecular cascades leading to the enhanced PSA-NCAM expression found after antidepressant treatment.…”
Section: Functional Implications Of Fluoxetine Treatment and Structurmentioning
confidence: 99%
“…The polysialylated form of NCAM (PSA-NCAM) plays a critical and unique role during brain development and in some brain tumors, modulating adhesion between cells, stimulating cell migration and neurite outgrowth (7,8). Observations based upon enzymatic digestion of PSA by endoneuraminidase (EndoN) (9), knock out of the polysialyltransferase coding genes responsible for addition of PSA to NCAM (10), or the use of mimotope peptide of PSA (11) indicate that the carbohydrate, more than the core protein, is critical to account for PSA-NCAM biological functions. At the molecular level, previous studies have demonstrated that PSA doubles the hydrodynamic radius of the extracellular domain of NCAM (12,13) and thereby increases the range and magnitude of intermembrane repulsion (14).…”
mentioning
confidence: 99%